The complete chloroplast genome of Abeliophyllum distichum Nakai (Oleaceae), cultivar Ok Hwang 1ho: insights of cultivar specific variations of A. distichum. Issue 1 (2nd January 2019) - Park, Jongsun; Kim, Yongsung; Xi, Hong; Jang, Taewon; Park, Jae-Ho
Abstract: Abeliophyllum distichum Nakai is the only species in Abeliophyllum genus, which is Korean endemic. Ok Hwang 1ho, the first official cultivar of A. distichum ., displays that colour of corolla is light yellow (8D and 9D). Here, we completed chloroplast genome of A. distichum cultivar Ok Hwang 1ho to understand genetic diversity of A. distichum cultivar. Its length is 156, 008 bp long and has four subregions: 86, 773 bp of large single copy (LSC) and 17, 827 bp of small single copy (SSC) regions are separated by 25, 704 bp of inverted repeat (IR) regions including 133 genes (88 protein-coding genes, eight rRNAs, and 37 tRNAs). The overall GC contents of this chloroplast genome are 37.8% and in the LSC, SSC, and IR regions are 35.8%, 31.9%, and 43.2%, respectively. Ninety-three single nucleotide polymorphisms (SNPs) and 56 insertion and deletions (INDELs) are identified against previous A. distichum chloroplast genome. Phylogenetic trees show that A. distichum is clustered with two Forsythia species and many cultivars of Olea europaea subspecies present shorter branches than that of A. distichum . Our chloroplast genome will be a fundamental data to understand morphological diversity of A. distuichum.